2016
DOI: 10.1038/srep21859
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ERK phosphorylation through oxidative stress is involved in the mechanism underlying sevoflurane-induced toxicity in the developing brain

Abstract: In animal models, neonatal exposure to general anesthetics significantly increased neuronal apoptosis with subsequent behavioral deficits in adulthood. Although the underlying mechanism is largely unknown, involvement of extracellular signal-regulated kinases (ERKs) is speculated since ERK phosphorylation is decreased by neonatal anesthetic exposure. Importance of ERK phosphorylation for neuronal development is underscored by our recent finding that transient suppression of ERK phosphorylation during the neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Preclinical data suggest that anesthetic and hypnotic drugs such as halogenated agents and midazolam may affect brain development [24]. The GAS study [25] found no increase in adverse neurodevelopmental outcome in infants exposed to a short period of sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Preclinical data suggest that anesthetic and hypnotic drugs such as halogenated agents and midazolam may affect brain development [24]. The GAS study [25] found no increase in adverse neurodevelopmental outcome in infants exposed to a short period of sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…The GAS study [25] found no increase in adverse neurodevelopmental outcome in infants exposed to a short period of sevoflurane anesthesia. Long-term use of sevoflurane in children and its effect on neurological development remains unclear (24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears that the phosphorylation levels of ERK may be related to the dose of UVA and incubation time, although further study will be required for verification of this hypothesis. Decreased ERK phosphorylation induced by oxidative stress leads to toxic effects on brain development . Additionally, mouse neuronal apoptosis within 6 days after birth can be induced by the transient blockade of ERK activation .…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal ERK activation is a central mean of transducing neurotransmitter and neurotrophic signals, and thereby participates in a wide range of activities including neural survival, protection, and stress-related behavioral responses [23]. Suppression of MEK/ERK and mTOR phosphorylation is critically involved in the mechanism underlying anesthetic-induced toxicity in the developing brain [24-26]. In the current study, by performing western blot analysis, we found that sevoflurane inhibited the activation of MEK/ERK signaling, but has no impact on mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%